Long‐Channel Effects in Randomly Oriented Carbon Nanotube Thin Film Transistors - Hai‐Yang Liu; Panpan Zhang; Xianmao Cao; Yang Zhang; Jianping He; Maguang Zhu; Mengmeng Xiao; Zhiyong Zhang (Advanced Electronic Materials)
Abstract Carbon nanotube (CNT) thin film transistors (TFTs) have demonstrated great potential for application in highly sensitive biosensors and large‐area electronics. However, research on the electrical behavior of long‐channel CNT TFTs is lacking; thus, the purposeful improvement in the performance of biosensors or circuits is difficult. In this study, the electrical transport characteristics of ionic‐liquid‐gate CNT TFTs with channel lengths (Lch) ranging from 10 to 400 µm are investigated. The CNT TFTs present classical drift‐diffusion transport at on‐state with a carrier mobility of around 27 cm2 V−1 s−1. In the subthreshold region of the CNT TFTs, an abnormal Lch‐dependent subthreshold swing (SS) relationship, named as the long‐channel effect (LCE)is observed, where SS worsens with increasing Lch. The existence of the junctions between the CNTs results in an unconventional density of states for carriers and a large series resistance for sharing the gate voltage; this dominates the abnormal scaling behavior in the subthreshold region by degrading the electrostatic integrity. The discovery of the abnormal LCE can aid in the construction of device models and purposefully improve the performance of CNT TFTs for biosensors and other large‐scale electronic applications.